WILLINGNESS TO PAY: A PROXY TO PRODUCT PRICE - Nababan, Tongam Sihol; Panjaitan, Raya; Panjaitan, Ferry; Munthe, Kornel (Jurnal Manajemen dan Bisnis, 2021)
Information about willingness to pay (WTP) essentially aims to protect consumers from the abuse of monopoly power owned by companies in the supply of quality products and prices. The consumer’s WTP of a product can be an appropriate basis in determining the pricing policy for a product because he can reveal the true value or price of the product based on consumer perception. The price proxy with the WTP can still meet the assumption of the traditional demand model (Marshallian demand model) where the price is not set (regulated) by the government. WTP can be obtained by using a contingent valuation method.